Una mirada a la arquitectura moderna de Tunja: obra del Ingeniero Arquitecto Ernesto Muñoz Navarro - Pinilla Rodríguez, Marcela Eunice Jr; Toro Ospina, Alexandra Jr; Millares Caro, Rocío Margarita Jr; Melo Vera, Diana Carolina Jr; Alami Zambrano, Ana María Jr; Tovar Martínez, Brayan Faruk Jr; Daza Gómez, Robinson Jr (Universidad de Boyacá, 2026)
The research focused on modern architecture in Tunja (Colombia) during the second half of the 20th century, with attention to the work of Engineer Architect Ernesto Muñoz Navarro. This architect was part of the first generation of students in the Engineering-Architecture program at the National University of Colombia and used the principles of modern architecture to contribute to the modernization of Tunja at a crucial time for the country. Additionally, he developed his own architectural style and employed innovative construction and structural systems for the time (Pinilla Rodríguez, et al., 2022, p. 11).